DESIGN OF WEB MOBILE ACCADEMIC INFORMATION SYSTEM IN MTS ISLAMIYAH SCHOOL SUKOHARJO - Tiara, Seregia Reffa; Suyono, Suyono; Trisnawati, Trisnawati; Mukodimah, Siti (STIT AL MULTAZAM, 2020)
technology. At present, the Mts Islamiyah Sukoharjo School is delivering information to the general public which is still relatively simple, namely through the distribution of brochures and the installation of banners in various places. The purpose of this study is to design a mobile web-based academic information system at Sukoharjo Mts Islamiyah school using a Content Management System. In this study, it shows that the use of a website-based information system can be a publication revolution in opening up a wider range of school information to convey various types of information about the Sukoharjo Mts Islamiyah school.